Can rotational thromboelastometry predict septic disseminated intravascular coagulation? - Koami, Hiroyuki; Sakamoto, Yuichiro; Ohta, Miho; Goto, Akiko; Narumi, Showgo; Imahase, Hisashi; Yahata, Mayuko; Miike, Toru; Iwamura, Takashi; Yamada, Kosuke Chris; Inoue, Satoshi (Blood coagulation & fibrinolysis, 2015)
Rotational thromboelastometry (ROTEM), known as point-of-care testing, has been incorporated into various kinds of postsurgical management. However, the utility of ROTEM for rapid diagnosis of sepsis-induced disseminated intravascular coagulation (DIC) has not been investigated. This retrospective study includes 13 sepsis patients who underwent ROTEM in our emergency department in 2013. All patients were divided into two groups on the basis of the presence of DIC diagnosed by the Japanese Association for Acute Medicine (JAAM) DIC score. We evaluated the demographics, clinical characteristics, laboratory data, ROTEM test and outcomes for each patient. The correlations between JAAM DIC score and significantly different parameters by univariate analysis and receiver operating characteristic (ROC) analysis were performed to assess the accuracy of the variables. There were seven and six patients in the DIC group and non-DIC group, respectively. The DIC group showed significantly longer prothrombin times, international normalized ratio of prothrombin time and clotting times (CTs) in the EXTEM test, and higher fibrinogen and fibrin degradation products and D-dimer. The CT in EXTEM test was correlated more with JAAM DIC score (r = 0.798), than the standard coagulation test. These parameters were accurate predictors in the diagnosis of septic DIC, with an AUC of 0.952, and a cut-off value of more than 46.0 s, resulting in a sensitivity of 100.0% and a specificity of 83.3%. CT in the EXTEM test was a single reliable indicator of sepsis-induced DIC diagnosed by the JAAM DIC score, and strongly associated with severity of DIC.